2017
DOI: 10.1007/s10787-017-0331-6
|View full text |Cite
|
Sign up to set email alerts
|

Sitagliptin and liraglutide reversed nigrostriatal degeneration of rodent brain in rotenone-induced Parkinson’s disease

Abstract: The present study investigated the possible relationship between pro-inflammatory cytokines and programmed nigral neuronal death in rotenone model of Parkinson's disease (PD). Sitagliptin and liraglutide efficacy to inhibit the inflammatory-apoptotic degenerative process were investigated, too. The experimental PD were induced in male albino rats by ten subcutaneously injections of rotenone (3 mg/kg/day, s.c). All treatment drugs were administered for 16 days after induction of Parkinson rat's model. Sitaglipt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(57 citation statements)
references
References 63 publications
3
53
0
1
Order By: Relevance
“…Under certain circumstances, autophagy is a stress adaptation that inhibits apoptosis and prevents cell death; however, in other cellular settings it constitutes another pathway of cell death. The results of the present study demonstrated that a low dose of liraglutide may be sufficient to reduce the expression of caspase-3 and Bax, and to increase the expression of Bcl-2, thus resulting in the reduction of apoptosis, which is similar to the results of a previous study by Badawi et al (39). According to the results of the present study, administration of liraglutide may activate autophagy while suppressing apoptosis.…”
Section: Discussionsupporting
confidence: 91%
“…Under certain circumstances, autophagy is a stress adaptation that inhibits apoptosis and prevents cell death; however, in other cellular settings it constitutes another pathway of cell death. The results of the present study demonstrated that a low dose of liraglutide may be sufficient to reduce the expression of caspase-3 and Bax, and to increase the expression of Bcl-2, thus resulting in the reduction of apoptosis, which is similar to the results of a previous study by Badawi et al (39). According to the results of the present study, administration of liraglutide may activate autophagy while suppressing apoptosis.…”
Section: Discussionsupporting
confidence: 91%
“…For example, exendin-4, a GLP-1 agonist, attenuated dopaminergic neuronal loss in MPTPinduced mouse model of PD by attenuating inflammatory and oxidative insults (Kim et al, 2009). Another GLP-1 agonist, liraglutide, a drug that is on the market as a treatment for type 2 diabetes, reversed nigrostriatal degeneration through anti-inflammatory, antiapoptotic, and neurotrophic mechanistic activities in PD-like rats induced by rotenone (Badawi, Abd El Fattah, Zaki, & El Sayed, 2017). Moreover, intrathecal injection of loganin in rats has been reported to attenuate formalin-induced tonic pain in an Ex9-39-reverse manner, suggesting the activation of spinal GLP-1R involved in the antinociceptive effects of loganin (Gong, Fan, Ma, Xiao, & Wang, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Lixisenatide (an incretin mimetic like exenatide, based on the structure of exendin-4) and liraglutide, dulaglutide and albiglutide (based on the structure of human GLP-1 and termed GLP-1 analogues). In PD models, data exists for liraglutide and lixisenatide which have similarly demonstrated neuroprotective effects in animal-toxin models of PD, preventing MPTP-, 6-OHDA-and rotenone-induced dopaminergic cell loss and motor impairments which were associated with reduction in pro-apoptotic signalling,pro-inflammatory cytokine production and promotion of neurotophic factors such as GDNF[129][130][131][132].…”
mentioning
confidence: 99%